2014
DOI: 10.1088/0031-9155/59/5/1283
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided microbeam irradiation to brain tumour bearing mice using a carbon nanotube x-ray source array

Abstract: Microbeam radiation therapy (MRT) is a promising experimental and preclinical radiotherapy method for cancer treatment. Synchrotron based MRT experiments have shown that spatially fractionated microbeam radiation has the unique capability of preferentially eradicating tumour cells while sparing normal tissue in brain tumour bearing animal models. We recently demonstrated the feasibility of generating orthovoltage microbeam radiation with an adjustable microbeam width using a carbon nanotube based X-ray source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Our compact microbeam system is different from the synchrotron irradiation system, since it electronically controls the radiation and thus allows real-time gated radiation delivery using respiratory or cardiac signals to accurately deliver the radiation under organ motions (15). An image-guided MRT protocol has been established for mouse brain tumor treatment, where magnetic resonance images were registered to the on-board X-ray radiography images of mouse brain to guide the delivery of microbeam radiation to the brain tumor with an average 450 µm accuracy (16). The current study used the same image-guided MRT protocol reported earlier, and aimed to evaluate radiobiological effects from MRT.…”
Section: Introductionmentioning
confidence: 99%
“…Our compact microbeam system is different from the synchrotron irradiation system, since it electronically controls the radiation and thus allows real-time gated radiation delivery using respiratory or cardiac signals to accurately deliver the radiation under organ motions (15). An image-guided MRT protocol has been established for mouse brain tumor treatment, where magnetic resonance images were registered to the on-board X-ray radiography images of mouse brain to guide the delivery of microbeam radiation to the brain tumor with an average 450 µm accuracy (16). The current study used the same image-guided MRT protocol reported earlier, and aimed to evaluate radiobiological effects from MRT.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The purpose of the compact x-ray tube based system is not to match the exquisite MRT dosimetry from the massive synchrotron facility based MRT systems. Our hypothesis is that the compact MRT system, especially future generation systems, can produce similar radiobiology response as the synchrotron-based MRT system.…”
Section: A Microbeam Radiation Therapymentioning
confidence: 99%
“…The five segments of electron source array are focused onto the surface of a common tungsten-rhenium anode with an energy 160 kVp. 12,13 The resulting reflective x-ray focal line, created by the five aligned linear electron beams bombarding the tungsten anode, was 142 µm by 160 mm after projection into an angle of 8…”
Section: A Compact Microbeam X-ray Systemmentioning
confidence: 99%
“…Targeted delivery of the microbeam to the brain tumor site in mouse has been demonstrated using a combined MRI and onboard x-ray projection imaging procedure. 20 Using the compact microbeam irradiator with an inevitably lower dose rate compared to what is used in synchrotron MRT experiments, it is necessary to minimize physiological motion induced microbeam blurring. MRT research so far is mainly focused on the brain tumors.…”
Section: B Compact Image Guided Mrt System For Small Animal Treatmentmentioning
confidence: 99%
“…20 The gate mesh, which is directly above the CNT substrates on the cathodes, is grounded, the anode is set to 160 kVp, and the cathodes are pulsed from ground to a negative voltage using a pulse generator to produce x rays at scheduled intervals. In regular experiments where gating is not used, the tube is operated at an 8% duty cycle using 500 μs width pulses.…”
Section: A Desktop Mrt Systemmentioning
confidence: 99%